Tradición, mito y naturaleza en la poesía de Raúl Gómez Jattin (2022)
Weaving analysis materials such as the poetic tradition and the force of the four elements, this essay takes on many of the central components of the work of colombian poet Raúl Gomez Jattin (1945-1997).